GAMBARAN BODY IMAGE, MINORITY STRESS, DAN GAY COMMUNITY STRESS LAKI-LAKI HOMOSEKSUAL DI JAKARTA - Parmenas, Marcell; Partasari, Wieka Dyah (Atma Jaya Catholic University of Indonesia, 2025)
This study explores the experiences of body image, minority stress, and gay community stress among homosexual men in Jakarta. Previous research suggests that homosexual men are more vulnerable to developing negative body image, with their sexual identity and involvement in the gay community creating additional layers of complexity in this process. Employing a qualitative approach with thematic analysis, data were gathered through semi-structured face-to-face interviews with four participants in their early twenties, all of whom identified as homosexual men over the age of 18 and represented diverse social backgrounds and community experiences. The findings show that body image formation is shaped by minority stress and gay community stress, both of which reinforce the idealization of masculinity. Minority stress stemmed from heteronormative cultural pressures that position masculinity as the normative ideal, while gay community stress originated within the community itself, where masculine bodies are often valued as the primary marker of social and sexual desirability. This dual pressure to appear masculine generated internal conflict which, when unmet, resulted in anxiety, feelings of undesirability, and negative self-evaluations about their physical appearances, further intensified by social media and dating applications. These findings highlight the importance of addressing the psychosocial experiences of homosexual men to inform more inclusive interventions.